The commercial job in Al-Mamoun district: (a study in urban geography) - Sabeeh, Mohammed (Al-Adab Journal, 2023)
The study aimed at analyzing the distribution of the commercial Function in Al-Mamoun district in Al-Karkh district in the city of Baghdad, by highlighting the size of this Function in every residential neighborhood within the sub-district. And analyze the change that occurred on commercial land uses in the study area. It was found that there is no fair distribution of commercial use in reviving the study area, there is a neighborhood in which all commercial services are specialized concentrated and accumulated, vocational and industrial areas, such as Al-Tamim and Al-Hatr, while we find other neighborhoods in which commercial use decreases in a way that is not commensurate with the size of the population in it, Such as the neighborhoods of (Zubaydah - Tabuk - Badr - Maysalun - Al-Buwaib). The researcher noticed that the central commercial area in the study area does not occupy a central location in the district, which facilitates access to most of the residents of the surrounding areas with it, where it is located on the northern side, which makes it relatively far from many neighborhoods. The researcher focused on the very large increase in the population in the research area for the period (2007-2019), which, therefore, constitutes pressure in the search area, especially from the service and commercial commodity requirements, which necessitates an expansion of commercial use in the search area in proportion to the volume of demand.